2021
DOI: 10.1016/j.ajem.2020.09.075
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation for acute hypoxemic respiratory failure in patients with COVID-19

Abstract: Aim Noninvasive ventilation (NIV) is known to reduce intubation in patients with acute hypoxemic respiratory failure (AHRF) [ 1 ]. We aimed to assess the outcomes of NIV application in COVID-19 patients with AHRF. Materials & methods In this retrospective cohort study, patients with confirmed diagnosis of COVID-19 and AHRF receiving NIV in general wards were recruited from two university-affiliated hospitals. Demographic, clinical, and laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 16 publications
(18 reference statements)
2
62
3
2
Order By: Relevance
“…Several previous studies described COVID-19 patients who underwent NIV outside ICU, often including patients receiving NIV as "ceiling" treatment (15,16,19,(21)(22)(23)28). Only a minority of these studies, however, reported the incidence of mortality of patients who were intubated after NIV failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies described COVID-19 patients who underwent NIV outside ICU, often including patients receiving NIV as "ceiling" treatment (15,16,19,(21)(22)(23)28). Only a minority of these studies, however, reported the incidence of mortality of patients who were intubated after NIV failure.…”
Section: Discussionmentioning
confidence: 99%
“…While previous investigations were focused on the outcome of NIV delivered out of ICU (15,16,19,(21)(22)(23)28), our study provides detailed information on the outcome of intubation after NIV failure. Worth remarking, our data do not allow drawing any conclusion on the bene ts of the application of NIV outside the ICU, as we do not consider the multitude of patients successfully treated with NIV in settings other than ICU in Veneto region during the study period (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AHRF was defined as partial oxygen pressure (PaO 2) <60 mmhg or oxygen saturation (SaO 2 ) less than 93% measured by pulse oximeter accompanied with respiratory distress symptoms and need for oxygen greater than 6 L/min. The patients with a partial arterial carbon dioxide (PaCO2) pressure higher than 50 mm Hg were excluded ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, we believe that PaO 2 /FiO 2 is a rather questionable option for predicting In our recent study, in COVID-19 patients receiving NIV outside the ICU, the baseline PaO 2 /FiO 2 index also did not differ between the success and failure groups, but we found that patients who failed NIV had higher minute ventilation on the first day of NIV (due to slightly higher tidal volume and higher respiratory rate) (6), which, of course, may increase the risk of self-inflicted lung injury (SILI). These findings are in line with Bellani's data, which also showed that the patients failing NIV had lower PaCO2 levels.…”
Section: To the Editormentioning
confidence: 63%